2012
DOI: 10.1021/jf3019886
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sensing of Total Antioxidant Capacity and Polyphenol Content in Wine Samples Using Amperometry Online-Coupled with Microdialysis

Abstract: This work describes the method for total antioxidant capacity (TAC) and/or total content of phenolics (TCP) analysis in wines using microdialysis online-coupled with amperometric detection using a carbon microfiber working electrode. The system was tested on 10 selected wine samples, and the results were compared with total reactive antioxidant potential (TRAP), oxygen radical absorbance capacity (ORAC), and chemiluminescent determination of total antioxidant capacity (CL-TAC) methods using Trolox and catechin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…The amperometric signals given by reference antioxidants such as caffeic acid and Trolox, at pH = 3.60 and 7.40 (obtained by adjusting artificial wine samples composed of 12 % ethanol and 0.05 M tartaric acid, with NaOH 1 M) were similar at 800 mV vs Ag/AgCl, showing that the recovery provided by the microdialysis probe was not pH dependent [137].…”
Section: Amperometrymentioning
confidence: 89%
See 1 more Smart Citation
“…The amperometric signals given by reference antioxidants such as caffeic acid and Trolox, at pH = 3.60 and 7.40 (obtained by adjusting artificial wine samples composed of 12 % ethanol and 0.05 M tartaric acid, with NaOH 1 M) were similar at 800 mV vs Ag/AgCl, showing that the recovery provided by the microdialysis probe was not pH dependent [137].…”
Section: Amperometrymentioning
confidence: 89%
“…It was found that, while the mean ratios between the antioxidant capacities of red and white wines were close for the amperometric, TRAP and ORAC methods (5.81, 4.36 and 5.76 Trolox Equivalents L -1 , respectively), the value determined by chemiluminescence was much greater (17.8 Trolox Equivalents L -1 ). This apparent disparity was considered to be a result of the red wine interferents' contribution impairing enzyme activity and of the smaller antioxidant capacity of white wines [137].…”
Section: Amperometrymentioning
confidence: 99%
“…The authors observed significantly higher antioxidant capacity of red wines compared to white wines. Jakubec et al [12] measured total antioxidant capacity and total polyphenol content of various brands of red, rosé, and white wines and observed highest concentrations of polyphenolic compounds in red wines compared to other wines. Antioxidant activity was highest in red wine, with one glass of red wine being equivalent to two glasses of white wine or two cups of black tea.…”
Section: Antioxidants Present In Winementioning
confidence: 99%
“…Structural changes in some of these compounds also occurred ORAC, oxygen radical absorption capacity measured as Trolox (TE) equivalent/L; TRAP, total radical trapping antioxidant parameter measured as TE equivalent/L. Source: Data from Jakubec et al [12].…”
Section: Antioxidants Present In Winementioning
confidence: 99%
“…Traditional Bulgarian wines have never been intensively studied [12][13][14][15][16][17]. This study provides a great opportunity to attempt fast classification in the direction of variety and geographic origin of wines produced in Bulgaria using Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%